Retrodictive and predictive attentional modulation in temporal binding. - Pedersen, Rasmus (Synthese, 2024)
This paper sets forward a novel theory of temporal binding, a mechanism that integrates the temporal properties of sensory features into coherent perceptual experiences. Specifying a theory of temporal binding remains a widespread problem. The popular ‘brain time theory’ suggests that the temporal content of perceptual experiences is determined by when sensory features complete processing. However, this theory struggles to explain how perceptual experiences can accurately reflect the relative timing of sensory features processed at discrepant times. In contrast, ‘event time theories’ suggest that the temporal content of perceptual experiences reflects the relative event time of external sensory features and that the brain accommodates differential processing times. We can formulate retrodictive and predictive versions of this theory. Retrodictive event time theories propose that we accommodate desynchronised processing retrodictively. Predictive event time theories propose that we accommodate desynchronised processing by predictively modelling the event time of sensory features. I argue that both views have strengths and weaknesses. This paper proposes a new hybrid theory that integrates these theories to accommodate these weaknesses. Firstly, I argue how retrodictions and predictions can interact in mutually beneficial ways to ensure speedy and accurate temporal binding. Secondly, I propose how attention plays a central role in flexibly selecting which contents get to be temporally bound. This theory can explain how prediction and retrodiction differentially affect temporal binding and, in turn, proposes a new way to understand temporal binding and has implications for how we should understand conscious experiences.